Molecular Polarizability Studies on Some Cyano-Biphenyl Series Liquid Crystals by Theoretical and Experimental Approach (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2019)
The transition temperatures of Cyano-biphenyl liquid crystalline compounds, (12.CB, 7O.CB and 5O.CB) are recorded by using Differential scanning calorimeter. The transition temperatures are used to estimate molecular polarizability by theoretical approaches, i.e., by Lippincott-delta function technique and molecular vibration technique. The density and refractive indices are measured by using specially designed Pyknometer and indigenously developed spectrometer coupled with small angled prism. The molecular polarizabilities are assessed by Vuks and Neugebauer methods using experimentally obtained refractive indices and density data. The results obtained by the current techniques and their limitations are discussed.
Keywords: Liquid crystals; Phase transition temperatures; Density; Refractive index and molecular polarizability